CORRELATION OF CYTOGENETICS AND GRADE OF BONE MARROW FIBROSIS IN PRIMARY MYELOFIBROSIS - Đorđević, Vesna; Peruničić-Jovanović, Maja; Šefer, Dijana; Bižić-Radulović, Sandra; Soldatović, Ivan; Todorović Balint, Milena (Srpski medicinski časopis Lekarske komore, 2025)
Introduction/Aim: Primary myelofibrosis is a clonal myeloproliferative neoplasm characterized by bone marrow fibrosis and extramedullary hematopoiesis. Fibrosis often complicates bone marrow aspiration and biopsy, further hindering disease diagnosis. Despite this, cytogenetic analysis is possible from bone marrow aspirate or peripheral blood. Karyotype is an independent prognostic parameter in primary myelofibrosis. The prognostic significance of bone marrow fibrosis grade in primary myelofibrosis remains debatable. This study aimed to investigate the impact of bone marrow fibrosis on overall survival in patients with primary myelofibrosis, as well as to examine the correlation between karyotype and bone marrow fibrosis grade in these patients. Materials and Methods: The study of the correlation between karyotype and bone marrow fibrosis grade included 120 out of 136 patients with primary myelofibrosis. We used the stratification of chromosomal abnormalities according to the recommendations of prognostic scoring systems: Lille, Mayo, International, and Dynamic International. Karyotype analysis was performed using the conventional cytogenetic method. Bone marrow biopsies of patients were stained using the Gordon-Sweet method. Results: In 136 patients with primary myelofibrosis, no statistically significant difference in survival was observed (p = 0.084) regardless of the bone marrow fibrosis grade. Additionally, no correlation was found between karyotype or chromosomal aberrations of varying risk levels and bone marrow fibrosis grade (Lille p = 0.293; Mayo p = 0.108; International Prognostic Scoring System p = 0.086; Dynamic International Prognostic Scoring System p = 0.613) in 120 patients with primary myelofibrosis. Conclusion: Although we did not establish a correlation between karyotype and bone marrow fibrosis grade, we believe that both parameters should be incorporated into new prognostic scoring systems for primary myelofibrosis.